Epidemiological and Clinical Characteristics of Adult RSV Infections: A Retrospective Analysis at University Hospital Center Zagreb (2022–2024) - Antonio Perčinić; Tara Vuletić; Nina Lizzul; Andrea Vukić Dugac; Ana Gverić Grginić; Irena Tabain; Dragan Jurić; Ana Budimir (Pathogens)
Respiratory syncytial virus (RSV) is a significant cause of respiratory infections in adults, particularly among older adults and individuals with chronic diseases. While traditionally linked to pediatric populations, RSV’s impact on adults, especially the elderly, is increasingly recognized but remains understudied in many regions. This retrospective study, conducted at the University Hospital Center Zagreb from October 2022 to April 2024, is the first to analyze RSV-positive adults in Croatia. Using RT-PCR testing, we evaluated clinical and epidemiological characteristics in both hospitalized and outpatient populations, focusing on those aged > 65 years. Among 2631 tested individuals, the RSV prevalence was 5.25%, with older adults experiencing the most severe outcomes, including pneumonia, COPD exacerbation, and intensive care admissions. Seasonal analysis confirmed a winter peak in RSV cases, while chronic conditions such as cardiovascular and respiratory diseases were strongly associated with higher complication rates. These findings demonstrate that older adults with comorbidities bear the greatest burden of RSV infection, highlighting the need for the early identification of high-risk patients. By providing detailed insights into RSV-related outcomes in this population, this study supports the development of targeted prevention and management strategies to reduce the burden of RSV in vulnerable groups.